Problems and opportunities for leveraging SME finance through value chains in Azerbaijan - Samir Aliyev (Asian Development Bank Institute (ADBI), 2019)
The paper discusses state, regulative framework, and recent developments in leveraging access to finance for micro, small, and medium-sized enterprises (MSMEs) in the Kyrgyz Republic through global value chain (GVC) examples in the Kyrgyz Republic. Access to finance in the Kyrgyz Republic is growing and demonstrates improvement of financial inclusion of companies SME sector in the Kyrgyz Republic as well as the sector of individual entrepreneurs and peasant farmers. Four selected value chains in agriculture, industry and service sector demonstrate the gaps in the access to finance of the MSME entities in the value chains supply to export markets. Some practical recommendations are proposed, aiming to decrease financial gaps for the SME sector in building resilient global value chain supplies.The paper outlines the contribution of small and medium-sized enterprises (SMEs) to Azerbaijan's economy, their access to finance, and the role of value chains in ensuring financing. The paper preparation process has shown that SMEs mainly benefit from bank loans, whereas there are some institutional, legislative, cultural and geographical factors limiting their access to finance. The low financial literacy rate of SME owner/managers and higher interest rates offered by banks are among the factors restricting SME access to finance. The government has strengthened legislation-in particular relating to institutions-in recent years to improve SME access to finance, but the effectiveness of this move is insufficient. This paper comprises eight sections: The contribution of SMEs to Azerbaijan's economy and the status of the financial sector; the financial inclusivity of SMEs; financial literacy levels; institutional, regulative, gender, cultural factors restricting SME finance; the structure of domestic value chain and Azerbaijan's role in global value chains; financial analysis of value chains; national strategies for SME finance; and key policy recommendations.
Keywords: G2; G3; G21; G28; O16; 330; Azerbaijan; SME; value chains; financial inclusion; financial literacy; loan; bank; financial institution